Return-to-play decisions - Laker, S. R. (Physical Medicine & Rehabilitation Clinics of North America, 2011)
Concussions occur as a result of forces directed to the head or neck, or from impulsive forces transmitted from the body to the head. They result in the rapid onset and spontaneous recovery of short-lived impairment of neurologic function. Concussions represent a functional, rather than structural, disturbance, and do not result in abnormalities on standard structural imaging. This article discusses a comprehensive approach to return to play in sports concussion, including managing athletes returning after prolonged postconcussion syndrome, multiple concussions, and intracranial hematomas and craniotomy.